1992
DOI: 10.1016/0014-5793(92)81237-g
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vascular smooth muscle cell growth by selective activation of the thrombin receptor Effect of heparin

Abstract: The synthetic peptide, SFLLRNPNDKYEPF, has been recently described as a peptide mimicking the new amino-terminus created by cleavage of the thrombin receptor, therefore acting as an agonist of the thrombin receptor. This peptide was a porect mitogen for rdbbit arterial smooth muscle -ells (SMC) and exhibited the same activity as that of native a-thrombin. Both compounds stimulated the proliferation of growth-arrested SMCs with half-maximum mitogenic responses at I nM. NAPAP. a synthetic inhibitor of the enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 15 publications
5
41
0
Order By: Relevance
“…While in vitro studies with vascular SMCs have identified several agents that stimulate their proliferation in culture, growth factors responsible for vascular injury-induced intimal SMC replication have only begun to be identified. Along with PDGF (28 -30) and bFGF (31), several enzymes of the coagulation cascade and fibrinolytic system are now considered to be likely candidates (3,5,(32)(33)(34)(35)(36). The first evidence for the involvement of fibrinolytic enzymes in such a process came from data by Clowes et al (7) showing that u-PA was expressed by vascular SMC during mitogenesis and t-PA during migration in an injured rat carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…While in vitro studies with vascular SMCs have identified several agents that stimulate their proliferation in culture, growth factors responsible for vascular injury-induced intimal SMC replication have only begun to be identified. Along with PDGF (28 -30) and bFGF (31), several enzymes of the coagulation cascade and fibrinolytic system are now considered to be likely candidates (3,5,(32)(33)(34)(35)(36). The first evidence for the involvement of fibrinolytic enzymes in such a process came from data by Clowes et al (7) showing that u-PA was expressed by vascular SMC during mitogenesis and t-PA during migration in an injured rat carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the key molecules involved in these processes are not known, several vasoactive agonists including angiotensin II (AII) and ␣ -thrombin have been implicated. These G-protein-coupled receptor (GPCR) agonists are potent mitogens for rat aortic smooth muscle (RASM) cells in vitro (1)(2)(3)(4)(5)(6) and also induce extracellular matrix formation (7)(8)(9)(10). AII acts by direct activation of the AII type 1 (AT 1 ) receptor (11), whereas ␣ -thrombin binds to its receptor and by enzymatic cleavage, generates a new amino terminus tethered ligand that activates the receptor (for review see ref- erence 12).…”
Section: Introductionmentioning
confidence: 99%
“…It is a potent cloned thrombin receptor and to induce platelet activation, Ca2+ activator of platelets [2] and presents a variety of functions upon fluxes in endothelial cells and platelets, or smooth muscle cell inflammatory and vascular cells. Thrombin is chemotactic for proliferation [16][17][18]. Since this ligand can only be generated by monocytes and mitogenic for lymphocytes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…mechanism of thrombin-induced mitogenesis. We therefore Thrombin has a direct mitogenic effect on rat neonatal and investigated the possibility that thrombin might induce mitobovine aortic smooth muscle cells, quiescent fibroblasts and genicity in endothelial cells via both thrombin cell receptorvascular endothelial cells [8,[11][12][13][14][15][16]. The enzymic activity of dependent and -independent pathways.…”
Section: Introductionmentioning
confidence: 99%